2018
DOI: 10.1038/s41398-018-0261-0
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological evidence for abnormal glutamate-GABA association following psychosis onset

Abstract: Previous studies have shown glutamatergic dysfunction and γ-aminobutyric acid (GABA)-ergic dysfunction in schizophrenia. Animal studies suggest that N-methyl-d-aspartate receptor (NMDAR) dysfunction and GABA-ergic dysfunction interact with each other and lead to alterations in excitatory/inhibitory balance. The NMDAR and GABAergic-interneuron functions may be indexed by mismatch negativity (MMN) and auditory steady-state gamma-band response (ASSR), respectively. However, no previous studies have tested the hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 77 publications
7
50
1
2
Order By: Relevance
“…The MMN is a negative-going peak reflecting the differences between scalp-level ERP responses to deviant vs. standard stimuli measured across a 135-205-ms time window and thought to reflect an automatic deviance detection process. Several studies have reported large effect sizes for MMN differences between schizophrenia patients and controls using electroencephalography (EEG;Hermens et al, 2010;Javitt et al, 1995;Koshiyama et al, 2017Koshiyama et al, , 2018bKoshiyama et al, , 2018cLight and Braff, 2005;Rasser et al, 2011;Salisbury et al, 2017;Wynn et al, 2010) or magnetoencephalography (Braeutigam et al, 2018;Yamasue et al, 2004), and these findings have been confirmed by several meta-analyses (Erickson et al, 2016;Umbricht and Krljes, 2005); These impairments are among the most consistently replicated findings in schizophrenia research (Keshavan et al, 2008;Näätänen et al, 2019). Many studies have also identified important associations between MMN and cognition (Koshiyama et al, 2018c;Rissling et al, 2014;Toyomaki et al, 2008;Wynn et al, 2010), negative symptoms and functional outcomes (Koshiyama et al, 2018c;Light and Braff, 2005;Rissling et al, 2014) in schizophrenia patients.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…The MMN is a negative-going peak reflecting the differences between scalp-level ERP responses to deviant vs. standard stimuli measured across a 135-205-ms time window and thought to reflect an automatic deviance detection process. Several studies have reported large effect sizes for MMN differences between schizophrenia patients and controls using electroencephalography (EEG;Hermens et al, 2010;Javitt et al, 1995;Koshiyama et al, 2017Koshiyama et al, , 2018bKoshiyama et al, , 2018cLight and Braff, 2005;Rasser et al, 2011;Salisbury et al, 2017;Wynn et al, 2010) or magnetoencephalography (Braeutigam et al, 2018;Yamasue et al, 2004), and these findings have been confirmed by several meta-analyses (Erickson et al, 2016;Umbricht and Krljes, 2005); These impairments are among the most consistently replicated findings in schizophrenia research (Keshavan et al, 2008;Näätänen et al, 2019). Many studies have also identified important associations between MMN and cognition (Koshiyama et al, 2018c;Rissling et al, 2014;Toyomaki et al, 2008;Wynn et al, 2010), negative symptoms and functional outcomes (Koshiyama et al, 2018c;Light and Braff, 2005;Rissling et al, 2014) in schizophrenia patients.…”
Section: Introductionmentioning
confidence: 90%
“…Standard (p = 0.90, 50-ms duration) and Deviant (p = 0.10, 100ms duration) tones were presented in pseudorandom order with a minimum of 6 Standard stimuli presented between each Deviant stimulus. The MMN amplitude at the Fz was measured using the mean voltage from 135 to 205 ms post stimuli in accordance with previous studies (Koshiyama et al, 2017(Koshiyama et al, , 2018b(Koshiyama et al, , 2018c). During the MMN and ASSR sessions, participants watched a silent cartoon video.…”
Section: Mismatch Negativitymentioning
confidence: 96%
See 2 more Smart Citations
“…Currently, there is robust evidence that both amplitude and phase of 40-Hz-ASSR is impaired in schizophrenia (12,13). There is mixed evidence, however, for the presence of 40-Hz-ASSRs deficits in both clinical high risk for psychosis (CHR-P) individuals (14,15) and patients with first-episode psychosis (FEP) (16).…”
Section: Magnetoencephalography (Meg) Positron Emission Tomography Amentioning
confidence: 99%